2021
DOI: 10.1080/1331677x.2021.1934508
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic, economic indicators and sectoral returns: evidence from US and China

Abstract: This study examines time-frequency connectedness between COVID-19 pandemic and economic indicators through a continuous wavelet transformation approach in the US and China. The study also assesses the dynamic conditional correlations (DCCs) between macroeconomic indicators and domestic sectoral returns during the pandemic. The findings display higher coherencies between COVID-19 and long-term predictive economic indicators in China compared to the US. Moreover, the results indicate that the stock market spillo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
0
14
1
Order By: Relevance
“…ECB and FED set their interest rate targets close to zero at the same time to minimize the effects of lockdowns and panic on overall economic activity [ 17 , 53 ]. As a result, it is apparent that the fundamental determinants of exchange rate dynamics have been substantially impacted by the COVID-19 pandemic [ 3 , 39 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…ECB and FED set their interest rate targets close to zero at the same time to minimize the effects of lockdowns and panic on overall economic activity [ 17 , 53 ]. As a result, it is apparent that the fundamental determinants of exchange rate dynamics have been substantially impacted by the COVID-19 pandemic [ 3 , 39 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The strengthening of the instability of the financial markets in the US is also confirmed by the research of Albulescu [12]. Qureshi's [13] research assessing the impact of the COVID-19 pandemic in the US on economic indicators showed that the pandemic had a strong impact on long-term forecast economic variables. On the other hand, the cost-benefit analysis of the first wave of COVID-19 in the US, from the state repression policies investigated by Broughel and Kotrous [14], showed that the total economic benefits in production from the beginning of April to 1 August 2020 ranged between USD 632.5 billion and USD 765 billion, while the cost of the repression policies ranged between USD 214.2 billion and USD 331.5 billion.…”
Section: Introductionmentioning
confidence: 67%
“…Market risk will also be affected by the pandemic, policy responses and macroeconomic fundamentals due to market volatility and changes in market return. However, the current strands of literature only focus extensively on examining the connectedness among different markets with the exposure to market risk from the Covid-19 pandemic, such as energy markets [ 17 , 18 ], infrastructure markets [ 20 ], stock markets [ 21 ], and economic indicators [ 19 ]. Key findings from these studies suggest that the Covid-19 pandemic intensified the connectedness among the markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Uddin et al [ 21 ] present a significant predictive power from the world financial index to the regional market indices. Regarding predictability, Qureshi [ 19 ] finds that the Covid-19 pandemic significantly affects the long-term predictive economic variables, which can portend the future economic state.…”
Section: Literature Reviewmentioning
confidence: 99%